2013
DOI: 10.1371/journal.pone.0070071
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Painting in Three Species of Buteoninae: A Cytogenetic Signature Reinforces the Monophyly of South American Species

Abstract: Buteoninae (Falconiformes, Accipitridae) consist of the widely distributed genus Buteo, and several closely related species in a group called “sub-buteonine hawks”, such as Buteogallus, Parabuteo, Asturina, Leucopternis and Busarellus, with unsolved phylogenetic relationships. Diploid number ranges between 2n = 66 and 2n = 68. Only one species, L. albicollis had its karyotype analyzed by molecular cytogenetics. The aim of this study was to present chromosomal analysis of three species of Buteoninae: Rupornis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…The first reciprocal chromosome painting experiments between chicken and a bird of prey ( Leucopternis albicollis ) confirmed the occurrence of multiple fissions of GGA1, GGA2, GGA3, as well as reinforced the chromosome signature GGA1pter/GGA6 as a synapomorphy shared by four different Buteoninae species, illustrating the importance of the use of comparative chromosome painting in phylogenetic and evolutionary studies [10], [12].…”
Section: Introductionmentioning
confidence: 87%
“…The first reciprocal chromosome painting experiments between chicken and a bird of prey ( Leucopternis albicollis ) confirmed the occurrence of multiple fissions of GGA1, GGA2, GGA3, as well as reinforced the chromosome signature GGA1pter/GGA6 as a synapomorphy shared by four different Buteoninae species, illustrating the importance of the use of comparative chromosome painting in phylogenetic and evolutionary studies [10], [12].…”
Section: Introductionmentioning
confidence: 87%
“…Studies that have mapped the chromosomal location of 45S rDNA sites have shown considerable divergence among birds (Nishida-Umehara et al, 2007;Nishida et al, 2008Nishida et al, , 2013Nie et al, 2009;Tagliarini et al, 2009;de Oliveira et al, 2013;Kretschmer et al, 2014;. In Paleognathae birds, the 45S rDNA is normally found in a single microchromosome pair (Nishida-Umehara et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…They were reported in several primates, cattle, reindeer, Chinese hamster, dog, and mouse [Di Berardino et al, 1983;Lin et al, 1984;Smeets and van de Klundert, 1990;Gripenberg et al, 1991;Stone and Stephens, 1993;Ruiz-Herrera et al, 2002;Helmrich et al, 2006]. There is abundant literature on the chromosomes of birds [Belterman and De Boer, 1984;de Oliveira et al, 2013;Nie et al, 2015], including that of BrdU treatments, but no fragile sites were noticed [Schmid et al, 1989;Nishida-Umehara et al, 1999]. In the course of control chromosome studies of our growing cell bank, we were surprised to detect multiple recurrent breakages in 2 chromosomes of a male blackbird Turdus merula Linnaeus, 1758 (Passeriformes: Turdidae) in fibroblast cultures treated by low doses of BrdU.…”
mentioning
confidence: 99%